Code of the West - Latham, Aaron (New York Simon & Schuster, 2001)
"Begins when Jimmy Goodnight, a young, earnest cowhand, recovering from having been brutally abducted by Comanches who slaughtered his family, sets his life on a new and surprising course by visiting a county fair. There he agrees to try to pull out an ax that has been deeply imbedded in an anvil and that has defied the efforts of the strongest men in Texas."--Jacket
84920
Keywords: Triangles (Interpersonal relations) -- Fiction; Arthurian romances -- Adaptations; Texas -- Fiction; Western stories; Love stories